INISIASI PENGGUNAAN PERPUSTAKAAN DESA WISATA DIGITAL BERBASIS APLIKASI ANDROID UNTUK MENINGKATKAN LITERASI PARIWISATA MASYARAKAT DESA PANTAI MEKAR - Kabbaro, Hurriyyatun; Tarma; Wal Marjan, Lu'lu'; Putri, Putri Mevia (Bahasa Indonesia, 2023)
Muaragembong is a sub-district in Bekasi Regency, West Java, Indonesia, with tourism potential. However, the potential of the existing area needs to be adequately optimized. Some of the problems identified are tourism in Pantai Mekar Village, which is still not optimal, the community's knowledge about tourism is low, the community does not yet understand the importance of knowledge for developing tourism, Pantai Mekar Village does not yet have a village library, and conventional libraries are less attractive to the community, especially for millennials. The community service activity was the Initiation of the Use of the Android Application-Based Digital Tourism Village Library to Increase Tourism Literacy in the Community of Pantai Mekar Village. This service activity uses Pustaka Wisata, a digital application library developed by researchers to be utilized by the people of Pantai Mekar Village. This activity involved ten teachers from a public elementary school in Pantai Mekar Village. Socialization activities and initiation of the use of the Tourism Library Application were carried out on August 15, 2023. The activities included preparing, socializing, and trialling the Tourism Library Application and filling out technology acceptance instruments and intentions to use technology. The service activity begins with the socialization of the Pustaka Wisata. Participants were also explained how to download and use the Pustaka Wisata. The results of the data analysis showed that all participants (100%) had acceptance and intention to use the Pustaka Wisata in the high category. It means that the community and the community can accept the Pustaka Wisata and also has a high intention to use it. The limitation of this service program is the instability of the internet signal, which is a resource for accessing applications. The researcher recommends that the government and the private sector increase internet access for the people of Pantai Mekar Village, which can encourage access and community empowerment in obtaining information and knowledge.